Melissa officinalis Extract Improves Spatial Memory and Cognitive Flexibility in a Valproic Acid-Induced Rat Model of Autism Spectrum Disorder: Evidence from Y-Maze Performance - Ali Neamah, Noor; J. Al-Bazii, Sinaa; Yahya Idrees Almuhanna, Muhannad (Kerbala Journal of Nursing and Health Sciences., 2025)
Cognitive impairments, especially spatial memory and cognitive flexibility deficits are core yet therapeutically disregarded aspects of autism spectrum disorder (ASD), and there are no approved drugs that specifically address those areas even though they have a significant effect on adaptive functioning. This experiment assessed the therapeutic value of ethanolic M. officinalis extract on hippocampal-dependent cognitive function in a validated prenatal rat model of ASD with valproic acid (VPA) induced ASD. On gestational day 12.5, pregnant Wistar rats were injected with VPA (600mg/kg, subcutaneously) or saline, and male offspring were injected daily with M. officinalis extract (100mg/kg, oral) or vehicle between postnatal days 35-82. Complementary Y-maze paradigms were used to determine cognitive performance as PND 83, including spontaneous alternation (spatial working memory and cognitive flexibility) and spatial reference memory (60 min retention interval). The exposure to prenatal VPA resulted in severe cognitive impairments where spontaneous alternation has dropped to 22.41% and discrimination index dropped to 0.288. M. officinalis daily treatment led to spectacular cognitive restoration with alternation performance increasing to 41.89% almost twice and discrimination index increasing to 0.708, an improvement of 145% and bettering no-exposed controls by nearly 72%. Intrinsic cognitive-enhancing properties were also supported by the fact that extract-treated control animals also showed better results. According to GC-MS, a-terpineol was the major constituent (29.898%). These results indicate that M. officinalis extract plays a significant part in reducing VPA-induced impairments in spatial working memory and cognitive flexibility, which justifies its translational prospects as a multi-target botanical intervention that targets the critically underrepresented area of cognition impairment in ASD.